Infectious episodes before and after a marathon race - Ekblom, B.; Ekblom, Ö.; Malm, C. (Scandinavian Journal of Medicine & Science in Sports, 2006)
The aim of this study was to investigate the incidence of self-reported infectious episodes (IE) during 3 weeks before (pre-IE) and 3 weeks after (post-IE) a marathon race and relate these figures to training status, running time, socioeconomic and demographic factors. Two questionnaires, including questions about important factors for IE incidence, were given to a representative cohort of 1694 runners (17% of all finishers) in the Stockholm Marathon 2000.